Mapping Attitudes Towards the Police at Micro Places - Wheeler, Andrew P. (Journal of quantitative criminology, 2020)
We examine satisfaction with the police at micro places using data from citizen surveys conducted in 2001, 2009 and 2014 in one city. We illustrate the utility of this approach by comparing micro- and meso-level aggregations of policing attitudes, as well as by predicting views about the police from crime data at micro places.